A New Component of the Fraser Complex - Hiroyasu, Sho (2014)
In embryos, the Fraser Complex (FC) mediates epithelial-connective tissue interactions. Loss of expression of FC components leads to Fraser Syndrome (FS) in which cohesion of epithelial tissues and stroma is perturbed. Using zebrafish, Richardson et al (in this issue) identified the protein AMACO in the FC. We discuss the utility of zebrafish in determining FC functions and identifying FS targets.